As modernidades visíveis e as alterações citadinas na Passo Fundo de outrora (1891-1924) - Ulrich, Raíssa Gehring (2020)
The city of Passo Fundo, located in the north of the state of Rio Grande do Sul, is currently a regional hub for health, service provision and commerce. Since the 1950s, its leaders have sought to consolidate the imagination of the plateau's capital1, as a regional reference. However, the desire, discourses, intentions and practices of modernizing urban space were factors already present in previous periods. This research aims to analyze the changes in urban daily life in Passo Fundo based on the speeches of managers and intellectuals linked to the narrative of modernity and city progress. The delimited period corresponds to 1891, the year the town was elevated to city status until 1924, the year the last municipal Code of Postures was published during the First Republic period (1889-1930). The aim is to contextualize the changes in the urban environment of Passo Fundo, analyzing discourses and modernizing practices, in order to verify their impacts on everyday life.